Size Effect on the Structural and Magnetic Properties of Nanosized Perovskite LaFeO3 Prepared by Different Methods - Nguyen Thi Thuy; Dang Le Minh (Advances in Materials Science and Engineering)
Nanosized LaFeO3 material was prepared by 3 methods: high energy milling, citrate gel, and coprecipitation. The X-ray diffraction (XRD), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA) show that the orthorhombic LaFeO3 phase was well formed at a low sintering temperature of 500°C in the citrate-gel and co-precipitation methods. Scanning electron microscope (SEM) and transmission electron microscope (TEM) observations indicate that the particle size of the LaFeO3 powder varies from 10 nm to 50 nm depending on the preparation method. The magnetic properties through magnetization versus temperature M(T) and magnetization verses magnetic field M(H) characteristics show that the nano-LaFeO3 exhibits a weak ferromagnetic behavior in the room temperature, and the M(H) curves are well fitted by Langevin functions.